2021
DOI: 10.1098/rstb.2019.0672
|View full text |Cite
|
Sign up to set email alerts
|

Non-human primates use combined rules when deciding under ambiguity

Abstract: Decision outcomes in unpredictable environments may not have exact known probabilities. Yet the predictability level of outcomes matters in decisions, and animals, including humans, generally avoid ambiguous options. Managing ambiguity may be more challenging and requires stronger cognitive skills than decision-making under risk, where decisions involve known probabilities. Here we compare decision-making in capuchins, macaques, orangutans, gorillas, chimpanzees and bonobos in risky and ambiguous contexts. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…That is, for instance, simply dividing the hidden area of our task in half rather than making a more profound calculation. Heuristics are crucial in complex situations because they are simplified decision rules that help individuals deal with problems requiring high cognitive investment 38,39 . Compared with younger adults, older adults show different parietal activity when faced with a decision under uncertainty probability associated with another heuristic 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, for instance, simply dividing the hidden area of our task in half rather than making a more profound calculation. Heuristics are crucial in complex situations because they are simplified decision rules that help individuals deal with problems requiring high cognitive investment 38,39 . Compared with younger adults, older adults show different parietal activity when faced with a decision under uncertainty probability associated with another heuristic 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies indicate that nonhuman primates show ambiguity aversion as adult humans, revealing that this situation entails a high cognitive cost 3,4 . Interestingly, most primates species use simple heuristics to face ambiguous decisions, and only great apes consider the ambiguity of the information in the decision process 39 . In accordance, researchers in developmental neuroscience have shown that children do not show ambiguity aversion 41 as adults and adolescents 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Our first goal was to implement generalized linear mixed model (GLMM) trees to identify associations of variables that lead to different success rates. GLMM trees, described by Fokkema et al (2018), are particularly well fitted to animal cognitive studies involving decision-type data (for a detailed description and examples, see Danel et al, 2021; Romain et al, 2021). The GLMM tree algorithm identifies subgroups of observations (also called terminal nodes) that differ in success rate, taking into consideration the nested structure of the data set (subjects).…”
Section: Methodsmentioning
confidence: 99%
“…Our most recent study (Romain et al, 2021) used the same task, but also exposed individuals to ambiguous options. We expected individuals to make use of simple decision rules rather than attempting to evaluate the odds of winning or losing, thus expressing ambiguity aversion (with only partial information about the odds).…”
Section: Effect Of Uncertainty On Decisions Rules In An Exchange Taskmentioning
confidence: 99%